Pengaruh Literasi Keuangan, Fintech E-wallet, dan Gaya Hidup Hedonisme terhadap Perilaku Konsumtif Mahasiswa di Kota Surakarta dan Sekitarnya - Febriana Norchofifah Cahyani Azra; Indra Lila Kusuma; Wikan Budi Utami (Lembaga Yasin AlSys, 2026)
The development of the digital era, financial literacy, fintech e-wallet innovation, and hedonistic lifestyles have become phenomena that influence people’s consumption behavior, particularly among young people. This study aims to examine the effects of financial literacy, fintech e-wallets, and hedonistic lifestyles on consumptive behavior. This study used a quantitative approach with a purposive sampling technique. Data were obtained by distributing questionnaires to 96 respondents. The results showed that, partially, financial literacy had no significant effect on consumptive behavior with a negative direction, while fintech e-wallets had no significant effect on consumptive behavior with a positive direction. Meanwhile, a hedonistic lifestyle had a significant effect on consumptive behavior with a positive direction. These findings indicate that respondents’ level of financial understanding has not been able to effectively control consumption behavior. In addition, the ease of using digital payment technology does not directly encourage consumptive behavior. Lifestyle factors, particularly an orientation toward pleasure and satisfaction, were proven to be more dominant in influencing consumption decisions. This study contributes to the development of studies on digital consumer behavior, especially in understanding the relationship between financial literacy, digital payment technology, and hedonistic lifestyles in the consumptive behavior of young people. As a practical implication, strengthening financial literacy needs to be accompanied by the development of awareness of consumptive lifestyles so that the use of digital financial services can be better controlled.